PENGARUH PENGETAHUAN INVESTASI, SUBJECTIVE NORM DAN PERCEIVED RISK TERHADAP NIAT INVESTASI LAGI MATA UANG PADA FORUM INVESTOR KRIPTO AXUSCOIN - Agus Malik; Agus Rahman A; Ike Kusdyah R (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2023)
Cryptocurrencies are increasingly in demand by investors as seen from the very significant increase in user ownership since 2018 which climbing from 35 million users in 2018, and then increasing to 101 million users in 2020 and 221 million users in 2021 (Statista.com, 2022). Axuscoin also played a role in providing humanitarian assistance by sending crypto money to victims of the Ukrainian war after the Ukrainian FIAT currency banking was not functioning, blocked by the Russian. Russian state authorities cannot reach crypto transactions because cryptocurrencies, especially Axuscoin, adhere to a decentralized controlled system that is free from state authorities in the world (Axuscoin Telegram forum, March). The Research Objectives are emphasizing in: 1) knowing and analyzing the effect of investment knowledge on the intention of investing again in the cryptocurrency Axuscoin, 2) knowing and analyzing the effect of subjective norm on the intention to invest again in the cryptocurrency Axuscoin, 3) knowing and analyzing the effect of perceived risk on the intention to invest again in the cryptocurrency Axuscoin. Method sampling according to Cooper & Emory (1995) is that if the number taken for a population whose exact number is unknown, the sample may be set at 100 respondents (crypto Axuscoin investors). The sampling technique is using non-probability sampling with purposive sampling method. The Research Results are 1) Investment knowledge has a positive effect on Investment Intention again for crypto Axuscoin investors, 2) Subjective Norm has a positive influence on Investment Intention again toward crypto Axuscoin investors, 3) Perceived Risk has a positive influence on Investment Intention again toward crypto Axuscoin investors.